STRATEGI HUMAS DAN PROTOKOL TERHADAP PUBLIKASI KEGIATAN DPRD DIY - Sulistyoningsih Sulistyoningsih (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2017)
Abstract. Public Relations (PR) DIY DPRD plays an important role on the publication of activities DIY DPRD. Unpublished activities of DIY DPRD will raise negatives suspicions from the public. In order to suppress the bad things, Public Relations DIY DPRD needs to have a strategy in publicizing the activities of Parlement DIY. The purpose of this research is to know the strategy used by DIY Public Relations Coordinator in publicizing the activities of DPRD DIY. Some strategies and Public Relations become the researcher in researching, so that the reserch can be focused more and more. The type of this research is descriptive qualitative research with data collections techniques in the form of participant observation, interview, and supported by document. The result of this study indicate Public Relations DIY DPRD or institutional data referred to as Public Relations and Protocol Parliament DIY has ten strategies in publishing the activities of DPRD DIY. These ten strategies include, legitlat Mimbar, Advertoria/ Newspapers, Mass Media Mass, Suplement (koran), Radio Interactive Diolog, Live Broadcast Radio, Television Broadcast, TV Magazine, Website, Press Conference and Media Center.